التمويل غير التقليدي كاداة لتغطية عجز الموازنة العامة في الجزائر دراسة تحليلية للفترة 2017-2022 - محمد البشير تنوس; خليفة شكة (university of eloued جامعة الوادي, 2025)
"شهدت الجزائر خلال السنوات الأخيرة ظروفاً اقتصادية ومالية استثنائية، خاصة التراجع الحاد في الإيرادات النفطية، ما أدى إلى تفاقم عجز الموازنة العامة، وفي هذا السياق، لجأت السلطات الجزائرية إلى تبني آلية التمويل غير التقليدي كأداة من أدوات السياسة النقدية غير التقليدية، حيث تم تعديل قانون النقد والقرض في عام 2014 للسماح للبنك المركزي بتمويل مباشر للخزينة العمومية تهدف هذه الدراسة إلى تحليل مدى مساهمة هذه الآلية في تمويل عجز الموازنة العامة خلال الفترة الممتدة من 2017 إلى 2022، مع التركيز على فعالية هذا البرنامج ومدى تحقيقه للأهداف الاقتصادية والنقدية المرجوة، وقد أظهرت نتائج الدراسة أن التمويل غير التقليدي ساهم في تغطية جزء معتبر من العجز وتوفير موارد مالية هامة على المدى القصير، إلا أنه أدى أيضاً إلى عدة آثار سلبية من بينها ارتفاع معدلات التضخم وتأكل احتياطي الصرف، مما يهدد الاستقرار الاقتصادي الكلي على المدى الطويل، وتسعى الدراسة إلى تقييم هذه السياسة من خلال رصد دوافع اعتمادها وتحليل نتائجها الاقتصادية، سواء السلبية أو الإيجابية، مع مقارنتها بالأهداف المسطرة لها ضمن سياق السياسة الاقتصادية العامة للبلا. In recent years, Algeria has witnessed exceptional economic and financial conditions, especially the sharp decline in oil revenues, which has exacerbated the public budget deficit. In this context, the Algerian authorities resorted to adopting the non-traditional financing mechanism as a tool of non-traditional monetary policy, as the Monetary and Loan Law was amended in 2014 to allow the Central Bank to directly finance the public treasury. This study aims to analyze the extent to which this mechanism contributes to financing the public budget deficit during the period from 2017 to 2022, with a focus on the effectiveness of this program and the extent to which it achieves the desired economic and monetary goals. The traditional financing mechanism contributed to covering a significant part of the deficit and providing important financial resources in the short term, but it also led to several negative effects, including high inflation rates and erosion of exchange reserves, which threaten macroeconomic stability in the long term. The study seeks to evaluate this policy by monitoring the motives for its adoption and analyzing its economic results, whether negative or positive, while comparing it with the goals set for it within the context of the
ماستر
Keywords: سياسة النقدية غير التقليدية التمويل; غير التقليدي; عجز الموازنة العامة; اقتصاد جزائري; unconventional monetary policy; unconventional financing; public budget deficit; Algerian economy.